2016
DOI: 10.1002/app.44691
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electron tomography of PLA/clay nanocomposites to understand the effect of the clays in the thermal stability

Abstract: Poly(lactic acid) (PLA) is one of the most promising bio-based and biodegradable polymers. However, its processability and range of applications are limited by its low thermal stability. The novelty of this work is studying the thermal stability of two PLA/clay nanocomposites (PLA/Cloisite 20A and PLA/Cloisite 30B) as a function of the composition and the microstructure, which is exhaustively studied by performing quantitative electron tomography (ET). Quantitative ET involves image acquisition, reconstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These authors observed the changes that nanocomposites presented when modifying extrusion, and injection molding processing parameters [15]. Several studies have been carried out on the preparation of nanocomposites based on PLA with cloisite for application as a water vapor barrier, antimicrobial properties [16], thermal properties [17] and mechanical properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed the changes that nanocomposites presented when modifying extrusion, and injection molding processing parameters [15]. Several studies have been carried out on the preparation of nanocomposites based on PLA with cloisite for application as a water vapor barrier, antimicrobial properties [16], thermal properties [17] and mechanical properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A Leica (SGiker, University of the Basque Country) Ultracut UCT cryo-ultramicrotome stage was used to cut 130-nm-thick slices from the middle and inner area of the A-type injection-molded samples (Figure 2) of each nanocomposite. 25…”
Section: Methodsmentioning
confidence: 99%
“…A threshold-based segmentation was carried out following the methodology previously reported in the literature. 25 The quantified microstructural parameters are described in Table 1 and Figure 3 and were calculated using Fiji free software. 31…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations